Analysis of Drug User Compliance in Tuberculosis Patients on Therapy Successat Puskesmas Medan Deli Medan City year 2022 - Putra Jaya Hulu; Masdalina Pane; Mido Ester J Sitorus; Kesaktian Manurung; Janno Sinaga (Science Midwifery, 2022)
According to WHO data, there were 6.3 million new pulmonary TB cases, this figure is the same as 61% of the incidence of tuberculosis in the world with a value of 10.4 million. The number of patients with TB increased the number of tuberculosis cases from the previous year, which was 9.6 million people. In addition, the number of deaths caused by tuberculosis worldwide is 40 people per 100,000 of the world's population. The aim of the research was to analyze the adherence of drug users in TB patients to the success of therapy at the Medan Deli Health Center in 2022. The population consisted of 112 pulmonary tuberculosis patients who were treated with a total sampling technique with a total of 112 respondents. The results showed that there was a relationship between adherence and successful therapy for TB patients (p = 0.000), there was a relationship between knowledge and successful therapy for TB patients (p = 0.000), there was no relationship between age and successful therapy for TB patients (p = 0.280), there was no gender relationship with successful therapy for TB patients (p= 0.856), there is a relationship between education and successful therapy for TB patients (p= 0.200), there is a relationship between work and successful therapy for TB patients (p= 0.003), there is a relationship between family support and successful therapy for TB patients (p = 0.010) and multivariate analysis that lack of compliance, lack of knowledge and not working has an effect on the failure of therapy.